Design of a 5.8 GHz unfolded lange coupler on the FR4 substrate - Hock G.C.; Chakrabarty C.K. (2023)
This paper describes the design of a 10 dB unfolded Lange coupler for operation at centering frequency of 5.8 GHz. The coupler is designed using the EDA software that has tuning and optimization features. The coupler is designed to have a coupling factor of 10 0.5 dB. in the design, microstripline is implemented. For the fabrication, FR4 substrate is used. 2005 IEEE.